Digital Culture and Its Impact on New Testament Interpretations and Religious Practices - Tari, Ezra; Revilla, Abdiel Enrique Sánchez (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Many aspects of life, including religious ideas and rituals, have been profoundly shaped by technology. It has affected how members of different faith communities interact and commune with God. These days, digital channels act as forums for conversations that could influence religious perspective. Here, the term